2018
DOI: 10.1002/jbio.201800186
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free non‐linear microscopy to measure myelin outcome in a rodent model of Charcot‐Marie‐Tooth diseases

Abstract: Myelin sheath produced by Schwann cells covers and nurtures axons to speed up nerve conduction in peripheral nerves. Demyelinating peripheral neuropathies result from the loss of this myelin sheath and so far, no treatment exists to prevent Schwann cell demyelination. One major hurdle to design a therapy for demyelination is the lack of reliable measures to evaluate the outcome of the treatment on peripheral myelin in patients but also in living animal models. Non-linear microscopy techniques which include sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…First, we imaged adult rat sciatic nerves 12 months after injection in newborn pups using Coherent Antistokes Raman Scattering (CARS) non-linear microscopy technique. This allows myelin sheath imaging without any labeling [21]. Using this technique on an intact nerve in a longitudinal view, we observed that the majority of transduced cells were myelinated cells ( Fig.…”
Section: Broad and Specific Transduction Of Msc Is Reached After Aav2mentioning
confidence: 92%
See 2 more Smart Citations
“…First, we imaged adult rat sciatic nerves 12 months after injection in newborn pups using Coherent Antistokes Raman Scattering (CARS) non-linear microscopy technique. This allows myelin sheath imaging without any labeling [21]. Using this technique on an intact nerve in a longitudinal view, we observed that the majority of transduced cells were myelinated cells ( Fig.…”
Section: Broad and Specific Transduction Of Msc Is Reached After Aav2mentioning
confidence: 92%
“…Second, we focused on the specific myelin defects observed in the CMT1A rat model using CARS imaging on freshly fixed nerves. Indeed, in a previous study, we had characterized CMT1A rat myelin sheath defects using this imaging technique [21]. The CMT1A myelin sheath showed a high heterogeneity compared to WT rat littermates: thin myelin sheath, demyelination ( Fig.…”
Section: Aav2/9-pmp22 Shrnas Reduce Myelinated Fibers Defects In Thementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we tested the anti-demyelinating effect of TRO19622 and the pro-demyelinating effect of MJ in vivo using CARS imaging of myelin as read-out for demyelination. Coherent Anti-stokes Raman Scattering (CARS) is a non-linear microscopy approach that allows imaging lipids, hence myelin, in vivo or ex vivo (37,38). First, two months old mice were treated with 3mg/kg of TRO19622 or vehicle subcutaneously for 5 consecutive days.…”
Section: The Release Of Mitochondrial Calcium Via Vdac1 Induces Schwamentioning
confidence: 99%
“…Four days after MJ injection or nerve crush, animal were sacrificed and their sciatic nerves were collected, washed by PBS and fixed for 1h in 4% PFA solution at room temperature. All CARS images were obtained as described previously (37) with a two-photon microscope LSM 7 MP coupled to an OPO (Zeiss, France) and complemented by a delay line (53). A ×20 water immersion lens (W Plan Apochromat DIC VIS-IR) was used for image acquisition.…”
Section: Cars Imaging and Image Analysismentioning
confidence: 99%